Core-shell PVA / gelatin nanofibrous scaffolds using multinozzle aqueous electrospinning - Şengör, Mustafa. (Thesis (Ph.D.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2019., 2019)
Biological scaffolds have been used in the reconstruction of the damaged tissues. They have similar morphology and structure to the host tissues. However, they can be produced using materials that can be harmful to humans and the environment. In this context, core-shell nano ber based sca olds, whose mechanical strengths are provided by PVA(poly vinyl alcohol) and recognition sites are provided by gelatin, were fabricated in a non-woven manner using multiple nozzles of electrospinning technique. Instead of widely used toxic, acidic or salt-based ionic solvents, deionized \water" was used as the only solvent for both polymers. Firstly, nano bers were produced from 8 % (w / w) gelatin and 8%(w / w) PVA solutions individually. Limits were determined for parameters such as voltage, feed rate, temperature and polymer concentrations. Although pure gelatin nano bers have diameters of less than 50 nm, they have beaded structure and have lower mechanical strengths. Smooth bers were obtained from 8% PVA. Fibers with PVA: gelatin core shell morphology were then produced at di erent feed rate ratios (FRR). Based on the ber diameter, the optimal FRR with a 15 kV voltage magnitude and 15 cm electrode distance was found to be 1: 1 with an average diameter of 280 nm. The ratio of 1: 3 and 1: 4 was seen as the formation of \beaded" bers and the pealing limit of gelatin over PVA, respectively. Mechanical and water resistance of the produced sca olds was further improved by cross-linking. Core - shell morphology was demonstrated by TEM, SEM, EDS analysis. The secondary structure of the gelatin from collagen and the e ects of the electrospinning were revealed by FTIR and DSC. Approximately 60% of all cross-linked sca olds were degraded in solution using lysozyme enzyme up to day 14.
Keywords: Tissues -- Analysis.; Tissues -- Plastic embedment.; Nanofibers -- Design and construction.